Критика концепції про переривання позовної давності після пред’явлення позову - Гуйван, Петро Дмитрович; Guyvan, Petro (ВД "Гельветика", 2019)
У статті розглядаються питання часового впливу на існування охоронного матеріального права на позов у разі його реалізації – пред’явлення домагання до суду. Обгрунтовується критичне ставлення автора до попередніх та нинішніх теоретичних концепції та існуючої правозастосовної практики, згідно з якими переривання позовної давності та початок нового давнісного перебігу після пред’явлення позову проявляється як загальне правило. Доводиться хибність даного підходу та невідповідність його реальній сутності охоронно-правових відносин, пов’язаних з юрисдикційним захистом порушеного права. Встановлено, що переривання позовної давності, як виключення, може відбутися після пред’явлення позову лише в конкретних випадках, чітко встановлених матеріальним законом.

The article deals with the issues of temporary influence on the existence of a protective substantive right to a lawsuit in the event of its implementation – the presentation of a claim to the court. We are convinced that the concept that the statute of limitations after filing a claim is interrupted by all claims to the same defendant arising from the subject matter and the validity of the harassment filed is not true. The rule of interruption and a new period of limitation after a lawsuit is not only inconsistent with the inner essence of the relations regulated by it, it leads to absolute uncertainty as to what kind of subjective right can be exercised during the new term. After all, the lawsuit harassment has already been implemented for the relevant specific requirements, and under current national legislation, its repeated implementation is impossible. In this paper, attempts to give some scientific explanation of this frankly unsuccessful legal configuration have been subjected to valid criticism. The author’s critical attitude to the previous and current theoretical concepts and the existing law enforcement practice, according to which the interruption of the limitation of actions and the beginning of a new period of limitation after filing a claim, manifests itself as a general rule. The erroneousness of this approach and the incompatibility of its real nature of the protective legal relations related to the jurisdictional protection of the violated right are argued. It proposes a reasonable conclusion that, based on the essence of the temporal characteristics of a person’s subjective right of claim, it is subject to only one-time implementation, and then the right itself is terminated, and the term for its implementation, as the lifetime of the subjective authority, which has ceased, also terminates. With this in mind, in law enforcement practice there should be no situations where the bringing of a claim will lead to the interruption of the limitation of actions for the same requirements to the same respondent. And this is a universal rule, the application of which does not depend on how the trial ended. It is established that the interruption of the statute of limitations, as an exception, can occur after the filing of a claim only in specific cases clearly established by material law. The only possible way to interrupt the period of limitation is the case when the claim is brought against one of several debtors, or, when the claim is only part of the claim to which the creditor has the right. At the same time, the limitation of actions is interrupted in relation to the claims against persons other than the defendant and with another subject. According to these requirements, not covered by the claim, a new period of limitation begins and ends.
Гуйван П. Д. Критика концепції про переривання позовної давності після пред’явлення позову / П. Д. Гуйван // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 12-17
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; позовна давність; переривання давності; припинення строку; limitation of actions; interruption of prescription; termination of term